An evaluation of the design of internal control over financial reporting for fiscal year 2021 in the ministry x - Ananda, Aditya; Wijayati , Nureni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The Audit Board of The Republic of Indonesia's (BPK RI) audit of the Ministry X’s 2020 Financial Statement and indicated an ICoFR weakness in the inventory account. This research intends to evaluate and analyze the ICoFR design at the Ministry X for account inventory based on the audit findings. It also assesses the Ministry X response to the auditor's recommendation of the 2020 Financial Statement audit findings. A case study methodology and qualitative technique are used in this research. Interviews, document examination, and literature reviews are the data collection methods used. According to the research's results, Ministry X neglected to identify some risk and control on the relevant accounts. As a result, improvements should be done to guarantee that similar auditor findings won't occur in the future.